The potential application of amplitude modulated ultrasound with infrared technique for blood glucose level determination in non invasive manner - Chowdhury K.; Srivastava A.; Sharma N.; Sharma S. (My University, 2025)
The advent of a truly new noninvasive technology for blood glucose level determinations could revolutionize management of diabetes along with increased patient compliance, decrease burden on medical emergency and diabetes related complexities. Herein, we have investigated the potential of using amplitude modulated ultrasound with Infrared techniques for blood glucose level determination In non invasive manner. This new noninvasive system with the operating wavelength of 940nm and ultrasound transmitter of 40 kHz has been used in 05 volunteers for the pilot studies. Standard procedures of the oral glucose tolerance test were conducted to check variations in the blood glucose levels. Blood samples for invasive blood glucose readings were obtained from the left hand fingers for every 15min up to 2 hours. Simultaneously noninvasive blood glucose readings were taken every 15min from the right hand fingers up to an entire time period of 2 hours. Overall 45 blood samples and 225 signals were recorded and examined in this pilot study. Close resembles observed between changes in the peak to peak voltage amplitude spectrum in frequency domain of noninvasively blood glucose measured values and the Invasive method utilized here. The degree of similarity between the observed signal and the blood glucose level is owing to the novel utilization of the amplitude modulated ultrasound wave (standing wave). It enhances the sensitivity, specificity of near infrared optical method for noninvasive blood glucose determinations. This pilot study indicates the potentiality of the amplitude modulated ultrasound with infrared techniques for the noninvasive blood glucose determinations in human volunteers.